PENETAPAN AWAL BULAN QAMARIAH MENURUT PERSPEKTIF AL-QUR’AN DAN HADITS - Farida Arianti (JURIS (Jurnal Ilmiah Syariah), 2018)
Determining the beginning of “Qamariah”that was known as “hilal” among moslem people because the order of doing fasting and breakfasting were dobe if they seeing the hilal. If they could not see the month, they had to complete (Rukyat) the on going month. It seemed that seeing the hilal was not the only one way in determining the beginning of “Qamariah”. In society, they could choose one of them that contribute to different result of determining the beginning of “Qamariah”. The happening of “Hadits”about the order to complete (Rukyat): “Berpuasalah kamu bila melihat hilal dan berbukalah kamu bila melihat hilal.” Different opinion among the moslem priests (Ulama) in Indonesia in understanding that “hadits” might forced moslem people to be in one side or the other side in doing fasting.